Pelatihan Pembuatan Pestisida Nabati Dari Daun Sirih Hutan Memberdayakan Petani Desa Pasir Agung dalam Mengendalikan Hama Tanaman Cabai Secara Ramah Lingkungan - Fitri Humairoh; Muhammad Rizki; Sabda Hidayat Hasibuan; Afiya Husni; Apni Nurdiansah; Ester Simanungkalit; Fadilla Lolicorima; Halimatus Sa’diyah; Indah Damai Yanti Sihombing; M. Nurfalisa; Mayi Bora Purba; Nur Susanti (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The continuous use of chemical pesticides in chili cultivation can cause negative impacts on the environment, human health, and the balance of the agricultural ecosystem. A safer and more sustainable pest control method is achieved through the utilization of botanical pesticides. This community service activity was conducted as part of the Universitas Riau Student Community Service (KKN) in 2026 at Pasir Agung Village, Bangun Purba District, Rokan Hulu Regency. The purpose of this activity was to improve farmers' knowledge and skills in producing and applying botanical pesticides made from wild betel leaf (Piper aduncum L.) to control chili crop pests in an environmentally friendly manner. The methods used included observation, counseling, demonstrations, hands-on practice, and evaluation. The results of the activity showed that the participants understood the benefits of botanical pesticides, were able to produce pesticide solutions independently, and demonstrated a commitment to reducing the use of chemical pesticides. This training also enhanced the utilization of local resources as raw materials for natural pesticides and encouraged the implementation of sustainable agriculture that is more economical, safe, and eco-friendly in Pasir Agung Village.